Experimental study of wheel-vehicle aerodynamic interactions. Issue 198 (March 2020) - Wang, Yifei; Sicot, Christophe; Borée, Jacques; Grandemange, Mathieu
Abstract: This work aims to provide a better understanding of the wheel-vehicle aerodynamic interaction, via experimental investigations on a 2/5-th scale vehicle equipped with 2/5-th scale rotating wheels. The findings demonstrate that the baseline configuration has a well-balanced wake, which means that the distribution of TKE in the symmetrical plane of the vehicle wake is symmetric in the upper and lower shear layers. This well-balanced wake can be easily modified by different wheel states or tire modifications, especially at the rear axle. This results from a global effect of the underbody momentum modifications. On the contrary, when the vehicle mean wake develops into a non-balanced topology, it is more robust towards underbody perturbations. By eliminating front wheels, the underbody flow momentum is vastly increased; by eliminating the underbody diffuser, the underbody flow momentum is significantly reduced. In these two circumstances, one can observe a robust downwash from the roof, independent of the wheel states or tire modifications. Besides, there is a more local effect of the wheels' near wakes on the aerodynamic lift and drag of the vehicle. Low pressure regions in the underbody downstream the wheels have an effect on vehicle lift. The rear wheel wakes interact with vehicle wake, imposing pressure conditions on the vehicle base, therefore influencing the vehicle drag. Highlights: Experimental investigations of wheel-vehicle aerodynamic interactions on model equipped with rotating wheels. Analysis of the wall pressure over the entire vehicle and of the velocity field in the model wake using PIV. Analysis of the effects of tire geometry and wheel rotation. Three distinct but interrelated aspects of wheel-vehicle aerodynamic interactions highlighting local effects near the tires and global effects in the wake.